Role of the Substrate in Feeding and Growth of the Marine Suspension-Feeding Gastropods Crepidula fornicata and Crepipatella peruviana. - Pechenik, Jan A.; Diederich, Casey M.; Chaparro, Oscar R.; Cubillos, Victor Mauricio.; Mardones-Toledo, Daniela A. (Tufts University. Tisch Library., 2017)
Unlike lamellibranch bivalves, suspension-feeding calyptraeid gastropods lack siphons and paired shell valves to regulate water inflow. This study was designed to determine if calyptraeid gastropods use the solid surface to which they attach to facilitate food particle capture. Juveniles of both Crepidula fornicata and Crepipatella peruviana were maintained with phytoplankton for 3 to 6 wk in the laboratory, either attached to solid substrate or without solid substrate. Individuals of C. fornicata and C. peruviana that were reared on solid substrate grew about five to ten times more, or two times more, respectively, than those deprived of solid substrate. Final tissue weights were also significantly greater for individuals of both species that had been reared on solid substrate. For the two species, phytoplankton clearance rates were about two to three times higher for individuals attached to solid substrate than for those without solid substrate; rates of food cord production from the gills were also significantly higher. About 50% of C. peruviana that were deprived of solid substrate died during the first 3 wk of observation, and about 60% were dead by 6 wk. In contrast, most individuals of C. peruviana that were attached to solid substrate survived for the entire 6-wk study period, and all of the C. fornicata survived whether or not they were attached to solid substrate. The solid substrate to which calyptraeid gastropods attach clearly plays an important role in their feeding biology, although the precise role remains to be explored.